Obywatele! Pod wysokim protektoratem Prezydenta [...]. (Gdańsk : [s.n.], 1947)
Afisz z programem obchodów 10.08.1947 r.
Keywords: Bierut, Bolesław -- (1892-1956).; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- źródła